Recurrent angioedema manifestation and treatment response in two patients from different families caring the myoferlin gene mutation: case series - Daria S. Fomina; Marina S. Lebedkina; Elena N. Bobrikova; Yulia D. Yukhnovskaya; Anna A. Roppelt; Olga A. Mukhina; Ulyana A. Markina; Yulia G. Alexeeva; Ekaterina A. Nikitina; Marcus Maurer; Alexander V. Karaulov; Maryana A. Lysenko; et al. (Orphanet Journal of Rare Diseases)
Abstract Data on hereditary angioedema with normal C1 inhibitor levels are currently limited. To date, only one Italian family with HAE-MYOF has been described, comprising exclusively female members. The angioedema (AE) of head and neck area with the teenage onset, triggered by menses and high fever episodes were identified. It is necessary to search for potential biomarkers in patients with HAE-MYOF. This case series reports two unrelated individuals from different families with symptoms onset of recurrent AE and identified myoferlin gene mutations. Due to limited knowledge about the clinical presentation, pathogenesis, and treatment response in HAE-MYOF, further data collection is essential.